Dosimetric Comparison Between Two and Six Beams Conformal Radiotherapy Plans for Paediatric Wilm's Tumour Patients at Ocean Road Cancer Institute, Tanzania - Mruma, Rashid M.; Dharsee, Nazima; Malichewe, Christina V.; Kisukari, Jumaa D.; Soko, Geofrey F.; Myanza, Hemed S.; Yoram, Furahini (Tanzania Journal of Science, 2023)
This study aimed to compare the dose distributions of three-dimensional conformal treatment planning using two and six radiation beams among paediatric patients receiving radiotherapy for Wilms tumour at Ocean Road Cancer Institute. CT scans of 53 patients were used to generate 106 treatment plans, 53 plans for two beams, and 53 plans for six beams. Planning target volumes and organs at risk parameters were compared between both plans using paired samples t-test. A p-value < 0.05 was considered statistically significant. The findings showed that the D95% and Dmean of the target are better with six beams than with the two-beam plans (p ˂ 0.001). The conformity index and monitor unit are significantly better with two-beam plans than with six-beam plans (p ˂ 0.001). No volume of the contralateral kidney received more than 12 Gy for both two and six plans. There were no differences in Dmax for the spinal cord (p = 0.208), while Dmean was observed to be lower in two compared to six beams (p ˂ 0.001) for the liver. Six beam plans have good target coverage, while two beam plans have good conformity index and monitor unit. The observed doses to the organs at risk in both plans were lower than their normal tolerance. Keywords: Wilm's tumour, Three-dimensional conformal radiotherapy, whole abdomen radiotherapy, paediatric radiotherapy, Dosimetry